2016
DOI: 10.1007/s11356-016-7718-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of Spirulina in mitigating hemato-toxicity in Swiss albino mice exposed to aluminum and aluminum fluoride

Abstract: Aluminum is ingested through foods, water, air, and even drugs. Its intake is potentiated further through foods and tea prepared in aluminum utensils and Al salt added in the drinking water for removal of suspended impurities and also fluoride in the affected areas. The ameliorating role of a blue green alga Spirulina is well documented to various pollutants in the animal models. We, therefore, examined its protective role (230 mg/kg body weight) on the hematology of male Swiss albino mice treated with aluminu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
1
2
Order By: Relevance
“…Regarding the leukocyte count, we did not find significant differences and this result contrasts with that previously reported by Sharma et al [59], who reported an increase in these blood cells, especially, in neutrophils and monocytes due to activation of the immune system in response to a foreign agent [59].…”
Section: Blood Cytometrycontrasting
confidence: 99%
See 1 more Smart Citation
“…Regarding the leukocyte count, we did not find significant differences and this result contrasts with that previously reported by Sharma et al [59], who reported an increase in these blood cells, especially, in neutrophils and monocytes due to activation of the immune system in response to a foreign agent [59].…”
Section: Blood Cytometrycontrasting
confidence: 99%
“…In these images, no morphological changes were observed in any of the study groups or cell types present in the smears. These results differ from those reported previously, where a high incidence of poikilocytosis was observed in the erythrocytes of the groups treated with aluminum [59,62]. Likewise, Bazzoni et al [42] observed a predominance of stomatocytes and the study published by Cheng et al [43] reported the presence of Heinz bodies in erythrocytes.…”
Section: Differential Blood Smear Analysiscontrasting
confidence: 59%
“…Aluminum is an active metal. When aluminum is exposed to air, an oxide film with a thickness of about 0.5 nm is formed on the surface, protecting the metal aluminum from further corrosion [16][17][18]. Aluminum is very soluble in strong alkali, and also soluble in dilute acid.…”
Section: Introductionmentioning
confidence: 99%